A survey of Australian and New Zealand clinical practice with neoadjuvant systemic therapy for breast cancer. Issue 6 (3rd June 2016) - Zdenkowski, N.; Butow, P.; Mann, G. B.; Fewster, S.; Beckmore, C.; Isaacs, R.; Douglas, C.; Boyle, F. M.
Abstract : Background: Neoadjuvant systemic therapy (NAST) has become an established treatment option for women with operable breast cancer. Aim: We aimed to better understand NAST treatment patterns, barriers and facilitators in Australia and New Zealand. Methods: We undertook a cross‐sectional survey of the current clinical practice of Australian and New Zealand breast cancer specialists. Questions included referral patterns for NAST, patient selection, logistics, decision making and barriers. Results: Of 207 respondents, 162 (78%) reported routinely offering NAST to selected patients with operable breast cancer (median 9% of patients offered NAST). Specialty, location, practice type, gender or years of experience did not predict for offering NAST. In all, 45 and 58% wanted to increase the number of patients who receive NAST in routine care and in clinical trials respectively. Facilitators included the multidisciplinary team meeting and access to NAST clinical trials. Specialist‐reported patient barriers included: patient desire for immediate surgery (63% rated as important/very important); lack of awareness of NAST (50%); concern about progression (43%) and disinterest in downstaging (32%). Forty‐three per cent of participants experienced system‐related barriers to the use of NAST, including other clinicians' lack of interest (27%); lack of clinical trials (24%) and unacceptable wait for a medical oncology appointment (37%). Conclusion: This group of Australian and New Zealand clinicians are interested in NAST for operable breast cancer in routine care and clinical trials. Patient‐ and system‐related barriers that prevent the optimal uptake of this treatment approach will need to be systematically addressed if NAST is to become a more common approach.